Production of citric acid by local isolates Aspergillus niger through solid state bioconversion of oil palm empty fruit bunches - Alam, Md. Zahangir; Bari, M.N.; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (2008)
An investigation was carried out to select the potential strain of Aspergillus niger for the production of citric acid from oil palm empty fruit bunches (EFB) through solid state bioconversion (SSB). This study evaluated the potentiality of twenty six wild strains of Aspergillus niger which were isolated from sewage treatment plant sludge, rotten lemon and orange. Factors considered in the evaluation process were citric acid production, sugar consumption and protein content as growth indicator. Two strains of Aspergillus niger (O-103A) and (O-114A) isolated from orange were found to have great potential with citric acid production 128.436.3 and 140.501 g/kg of dry EFB; sugar consumption 63.433.4% and 57.290.9% of initial sugar (50 g/kg of EFB); protein content as growth indicator 26.053.7 and 32.931.7 g/kg of treated EFB; pH evolution of 2.720 and 2.640 and bioconversion time 4 and 8 days, respectively. Therefore, the strains O-103A and O-114A can be used as the potential strains for the production of citric acid from EFB by solid state bioconversion.